Relationship between Teacher Self-Efficacy and Students Achievement at Primary Level - Noor Muhammad; Alia Khushi; Allah Bakhsh (JELM, 2024)
Self-efficacy is a way of a person to judge his own abilities to accomplish the assigned task. Self-efficacy is defined as the ability to give the required or wanted results. The teacher self-efficacy is openly related to make sure students achieving specific goals. Their self-efficacy supports them to apply the latest techniques within their teaching learning environment to certify student’s development and create fruitful academic achievement. Therefore, the plan of present study was to determine the relationship between teacher self-efficacy and students achievements. All the public primary school teachers of District Toba Tek Singh were considered for the target population of study. The 200 teachers of primary school including 88 male and 112 female were selected for the sample of study through propionate sampling technique. The data were collected after ensuring the validity and reliability of research tool. The analysed data revealed that community self-efficacy, school climate self-efficacy, and parental involvement self-efficacy had positive correlation with students’ achievement score. The results found a non-significant impact of different tehsils on the decision-making self-efficacy abilities and the instructional self-efficacy abilities. Different tehsils have same level of disciplinary self-efficacy. The results found a non-significant impact of different tehsils on the parental support self-efficacy and community self-efficacy. A non-significant impact of different tehsils on the school climate selfefficacy abilities and performance related self-efficacy